Modéliser les carrières et la reconnaissance artistiques : une prosopographie des peintres médaillés au Salon (1848-1880) - Claire Dupin de Beyssat (Humanités Numériques)
This article presents the site Les peintres médaillés au Salon (1848-1880). The database it accompanies documents the careers of the 619 artists who won a medal in the “Painting” section at the Salon de Paris between 1848 and 1880. It allows to consult their entire biographies and to browse a catalogue of more than 30,000 works. In the first part, the author presents the collection methodology and the sources used to gather the data. In the second part, she describes the different stages of construction of the database, first from the perspective of personal exploitation and then with a view to publication on the semantic Web. Finally, it reports on the affordances and potential uses of this database.